PENGEMBANGAN MEDIA PEMBELAJARAN DASAR DESAIN BERBASIS FLIP CHART MENGGUNAKAN PUZZLE DI SEKOLAH MENENGAH KEJURUAN - Risa Amelia; Siti Mariah; Enggar Kartikasari (Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to: 1. Develop basic learning media based on flip chart designs; 2. Knowing the feasibility of the media through expert validation; 3. Knowing the students responses to the flip chart media. This type of research is development research with a Four-D development model. The validators in this study consisted of material and media experts, as well as class X students as subjects. The object of this research is the basic learning media for flip chart-based design. The research instrument used was a questionnaire. The data analysis technique used quantitative descriptive analysis.The results showed that: 1. The development of flip chart-based media was carried out in 4 stages, including: a. Define, which is to determine the product to be developed; b. Design, namely making product designs; c. Development, namely developing products through validation of material and media experts and conducting small-scale trials totaling 5 students, as well as limited scale trials totaling 15 students; d. Disseminate is a tested product deployment stage; 2. The flip chart-based learning media developed based on the material expert's assessment was 86.45% in the very feasible category and the media expert's assessment of 77.70% was in the feasible category; 3. The response of students to the use of small-scale flip chart-based learning media is 84.59% in the very highcategory and the assessment on a limited scale of 77.02% is in the highcategory.